Al-Lughah al-‘Arabīyah fī Indūnīsīyā: Dirasah Taḥlilīyah ‘an Taṭawwurātihā wa Mushkilāt Ta’līmihā - Muhaiban, Muhaiban (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2006)
Arabic teaching in Indonesia started when Islam was introduced to this country in the 7th-8th Century. At that time Arabic was given merely for religious teachings and to teach student to read the HoIy Qur'an, say prayers, and read and understand religious books also known as